MANAJEMEN MUTU DALAM PENGEMBANGAN MADRASAH TSANAWIYAH (STUDI KASUS DI MTS WALISONGO 1 MARON PROBOLINGGO) - Aliwafa Aliwafa (PEDAGOGIK : JURNAL PENDIDIKAN, 2015)
The existence of madrassas is firmly rooted in the noble values and scientific tradition of Islam that is expected to be a solution to the double standards of education in Indonesia, between schools and public schools. People still look at it less interesting to the public schools more gemilau. This phenomenon led to the idea of modernizing madrasah education to match the general educational institutions are considered to have been dashed away. MTs have enough challenges vary given the shift in society's view of Islamic education.The quality of the reference quality education according to market demands. MTs Walisongo 1 Maron is one of the madrasah is the choice and demonstrate achievements in the past five years. Quality management has evolved from a measurement into a management system in madrassas. Quality management in the madrasah strived to utilize resources with the principle POACH oriented to quality.